2015
DOI: 10.3233/jnd-150092
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic use of Massively Parallel Sequencing in Neuromuscular Diseases: Towards an Integrated Diagnosis

Abstract: Massively parallel sequencing is revolutionizing the genetic testing in diagnosis laboratories, replacing gene-by-gene investigations with a “gene panel” strategy. This new approach is particularly promising for the diagnosis of neuromuscular disorders affecting children as well as adults, which is constrained by strong clinical and genetic heterogeneity. While it leads to a strong improvement in molecular diagnosis, this new approach is dramatically changing the whole diagnosis process, establishing new decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Since the identification of dominant mutations in the skeletal muscle ryanodine receptor (RYR1) gene as the cause of Malignant Hyperthermia (MH) in 1991 and CCD in 1993 9,10 , mutations in more than 20 genes have been identified. Introduction of next generation sequencing (NGS) techniques into routine clinical diagnosis 11 has resulted in an improved detection rate of mutations in genes such as RYR1, nebulin (NEB) or titin (TTN), due to their sheer size previously only studied with Sanger sequencing in few patients. These novel techniques have led to the recognition that different mutations in the same gene may give rise to variable histopathological phenotypes, whilst mutations in different genes may cause the same histopathological feature, often due to functional association of the defective proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Since the identification of dominant mutations in the skeletal muscle ryanodine receptor (RYR1) gene as the cause of Malignant Hyperthermia (MH) in 1991 and CCD in 1993 9,10 , mutations in more than 20 genes have been identified. Introduction of next generation sequencing (NGS) techniques into routine clinical diagnosis 11 has resulted in an improved detection rate of mutations in genes such as RYR1, nebulin (NEB) or titin (TTN), due to their sheer size previously only studied with Sanger sequencing in few patients. These novel techniques have led to the recognition that different mutations in the same gene may give rise to variable histopathological phenotypes, whilst mutations in different genes may cause the same histopathological feature, often due to functional association of the defective proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of cost and time effectiveness, and several quality control parameters, targeted sequencing has been accepted by several large‐scale studies as the method‐of‐choice in the neuromuscular disease (NMD) diagnostics (Ankala et al., ; Biancalana & Laporte, ; Gorokhova et al., ; Savarese et al., ; Vasli et al., ). However, defining the optimal size of the gene panel remains the biggest challenge in targeted sequencing (Volk & Kubisch, ).…”
Section: Introductionmentioning
confidence: 99%
“…Next generation sequencing techniques (NGS) provide a potential way to overcome diagnostic delays due to genetic heterogeneity and also the possibility to identify novel genetic causes of muscle disorders [ 13 , 14 ]. Several studies have reported on the application of gene panels [ 15 23 ] or WES [ 24 , 25 ] for the diagnosis in undiagnosed muscle disease, achieving diagnostic rates from 16 to 76%, with the highest diagnostic rate achieved in patients with no prior genetic testing [ 26 ].…”
Section: Introductionmentioning
confidence: 99%